Education and knowledge in diabetic nephropathy - Freitas, Cristina Cruvinel; Anjos, Laura Raniere Borges dos; Costa, Francine Pereira Higino da; Diniz, Matheus Carvalho; Reis, Angela Adamski da Silva; Santos, Rodrigo da Silva (Multi-Science Journal, 2018)
.